2008
DOI: 10.1063/1.2975207
|View full text |Cite
|
Sign up to set email alerts
|

Spectral mixing formulations for van der Waals–London dispersion interactions between multicomponent carbon nanotubes

Abstract: Recognition of spatially varying optical properties is a necessity when studying the van der Waals-London dispersion (vdW-Ld) interactions of carbon nanotubes (CNTs) that have surfactant coatings, tubes within tubes, andor substantial core sizes. The ideal way to address these radially dependent optical properties would be to have an analytical add-a-layer solution in cylindrical coordinates similar to the one readily available for the plane-plane geometry. However, such a formulation does not exist nor does i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Test calculations on several ceramic crystals showed that the calculated Hamaker coefficients using theoretical spectra do not differ much from those obtained using experimental spectra ͑Ahuja et al, 2004͒. Recently this approach has been applied to obtain Hamaker constants for both metallic and semiconducting single-wall carbon nanotubes ͑SWCNT͒ and multiwall carbon nanotubes ͑MWCNT͒ of different chiralities with considerable success ͑Rajter, Rajter et al, 2008͒. In Figs. 2 and 3 we show Љ͑͒ and the corresponding vdW-Ld spectra properties of ͓6,5,s͔ and ͓9,3,m͔ SWCNTs. It is important to capture all of these interband transitions, out to at least 30 eV, because all areas are adding to the overall summations and can shift the magnitude of the resulting Hamaker coefficients.…”
Section: Ab Initio Optical Properties Of Complex Materialsmentioning
confidence: 99%
“…Test calculations on several ceramic crystals showed that the calculated Hamaker coefficients using theoretical spectra do not differ much from those obtained using experimental spectra ͑Ahuja et al, 2004͒. Recently this approach has been applied to obtain Hamaker constants for both metallic and semiconducting single-wall carbon nanotubes ͑SWCNT͒ and multiwall carbon nanotubes ͑MWCNT͒ of different chiralities with considerable success ͑Rajter, Rajter et al, 2008͒. In Figs. 2 and 3 we show Љ͑͒ and the corresponding vdW-Ld spectra properties of ͓6,5,s͔ and ͓9,3,m͔ SWCNTs. It is important to capture all of these interband transitions, out to at least 30 eV, because all areas are adding to the overall summations and can shift the magnitude of the resulting Hamaker coefficients.…”
Section: Ab Initio Optical Properties Of Complex Materialsmentioning
confidence: 99%
“…Several experimental procedures have exploited the differences among these properties in order to separate SWCNTs by chirality ͑see Ref. 2 and references therein͒. In order to separate a polydisperse solution of SWCNTs into monodisperse fractions of one chirality reliably, one needs to understand the detailed features of the interactions between constituent SWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the finite thickness of the wall would require a more careful modeling of its effective dielectric response 3 and thus introduce additional parameters that would complicate the understanding of the retardation effects in van der Waals-dispersion interactions between this SWCNT and the half space, which is our primary aim in this article. Also, once the surface-to-surface separation between a SWCNT and the half space is greater than approximately two SWCNT outer diameters, 3 this approximation turns out to work quite well. In the case the ͑6,5͒ SWCNT, this would mean greater than 1.5 nm.…”
Section: Numerical Results For the Dispersion Interactionmentioning
confidence: 99%
“…2,3 Several experimental procedures have been proposed to exploit the differences between these properties in order to separate SWCNTs by chirality ͑see Ref. 3 and references therein͒. Different separation mechanisms have been suggested and tested 4 but we are still some way off to separate a nanotube mixture into its single chirality components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation